What If the Rival Drives a Porsche?: Luxury Car Spending as a Costly Signal in Male Intrasexual Competition. (5th December 2016) - Hennighausen, Christine; Hudders, Liselot; Lange, Benjamin P.; Fink, Hanna
Previous research found that men conspicuously consume luxury products to attract a mate and to signal their mate value. However, these studies have yet neglected to investigate the function of male conspicuous consumption in same-sex competition. Given that intersexual selection and intrasexual selection are closely related processes, it stands to reason that a further function of male conspicuous consumption could be to impress and deter same-sex rivals. An 2 (intrasexual competition context vs. control) × 2 (conspicuous luxury vs. inconspicuous nonluxury) between-subjects experimental study conducted with an Amazon Mechanical Turk sample ( N = 160) revealed that men reported both higher liking of and an intent to purchase a conspicuous luxury car compared to an inconspicuous nonluxury car due to increased feelings of social status. This effect was stronger in the intrasexual competition than in the control context. An additional perception study using a single-factor between-subjects design (conspicuous luxury vs. inconspicuous nonluxury car) among German men ( N = 405) indicated that male participants rated a man who displayed a conspicuous luxury car more as a rival and mate poacher and less as a friend. They further perceived him to be superior on various mate value characteristics (i.e., attractiveness, intelligence, ambition, and status) and rated him as more oriented toward short-term mating. In sum, our findings add to previous research in the field of evolutionary consumer psychology by suggesting that male conspicuous consumption of luxuries may also serve a function in male–male competition.